Effects of ammonium polyphosphate microencapsulated on flame retardant and mechanical properties of the rigid polyurethane foam. Issue 48 (2nd July 2020) - Cheng, Jiaji; Niu, Shaoshuai; Ma, Dan; Zhou, Yue; Zhang, Feng; Qu, Wenjuan; Wang, Dong; Li, Shaoxiang; Zhang, Xinlong; Chen, Xianqun
Abstract: In this article, a flame retardant microcapsule ammonium polyphosphate microencapsulated by polyurea (POAPP) was successfully synthesized by interfacial polymerization method using ammonium polyphosphate (APP) as core and polyurea as shell. The microencapsulation is observed by scanning electron microscopy and characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis and hydroscopicity test, which prove the success in synthesizing microencapsulation. When the POAPP is added into rigid polyurethane foam (RPUF), the flame retardant and mechanical properties are investigated using cone calorimeter, limited oxygen index test, and compressive strength test. The PHRR of RPUF‐POAPP20 decreased from 336.52 kW/m 2 (Ref. RPUF) to 203.84 kW/m 2 and the THR of RPUF‐POAPP20 was only 7.6 MJ/m 2, which is 33.9% lower than that of Ref. RPUF. Furthermore, the limiting oxygen index of RPUF‐POAPP20 reaches 24.8%, which increased by 36.3% compared to Ref. RPUF. Whereas the maximum compressive strength of RPUF‐POAPP5 was 7.46 MPa, which is higher than that of RPUF‐APP5. Abstract : Ammonium polyphosphate microencapsulated by polyurea.